Die intravenöse Leiomyomatose: eine seltene Tumorentität - Peters, Andreas; Bischoff, Moritz; Weitz, Jürgen; Longerich, Thomas; Böckler, Dittmar; Hyhlik-Dürr, Alexander (Gefässchirurgie, 2012)
The case is presented of a 67-year-old female patient who underwent surgery under the suspected diagnosis of a hemangioma located in the inferior vena cava. A histologically verified hemangioma of the right atrium had been previously resected in another hospital. The patient was asymptomatic at all times. Surgery was indicated after tumor progression and cardiac involvement. Intraoperatively the tumor could be entirely tracked along the inferior vena cava, the common and internal iliac veins down to its origin in the uterus. Total removal of the tumor together with hysterectomy and adnexectomy was accomplished. Histological analysis revealed the rare diagnosis of an intravenous leiomyomatosis.